2020
DOI: 10.31616/asj.2020.0147
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Use of Artificial Intelligence in Spinal Diseases

Abstract: Artificial neural networks (ANNs) have been used in a wide variety of real-world applications and it emerges as a promising field across various branches of medicine. This review aims to identify the role of ANNs in spinal diseases. Literature were searched from electronic databases of Scopus and Medline from 1993 to 2020 with English publications reported on the application of ANNs in spinal diseases. The search strategy was set as the combinations of the following keywords: “artificial neural networks,” “spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 79 publications
0
32
0
1
Order By: Relevance
“…Recent advances in artificial intelligence techniques have led to development of automated tools and application of machine learning algorithms in the field of spinal imaging [ 27 , 66 , 67 ]. In this study, we utilize a recently developed CNN model that segments seven bilateral cervical muscle groups (14 muscles in total) and measures muscle composition in each muscle group (Weber et.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in artificial intelligence techniques have led to development of automated tools and application of machine learning algorithms in the field of spinal imaging [ 27 , 66 , 67 ]. In this study, we utilize a recently developed CNN model that segments seven bilateral cervical muscle groups (14 muscles in total) and measures muscle composition in each muscle group (Weber et.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of different neural network algorithms could assist in selecting the best model with the best performance. Additionally, the advantages and disadvantages of different algorithms for each spinal disorder should also be considered (76). Therefore, future study should focus on the validation of ML models on heterogeneous test sets prior to deployment and the regulation of ML performance after deployment in clinical practice.…”
Section: Current Limitations and Future Directionsmentioning
confidence: 99%
“…Thirdly, concept shifting from human vs. machine to human-and-machine may be essential to over these barriers. Take an example, there were four studies concluded that ML combining with clinical decision making is superior to ML models or clinical decision making alone (72,(76)(77)(78). Using the experience of clinicians as a prerequirement, the application of ML in spine deformity, such as scoliosis, will be more promising in increasing the accessibility of clinical data.…”
Section: Current Limitations and Future Directionsmentioning
confidence: 99%
“…Therefore, automated detection of frequent pathologies, especially in common projection radiography, will help maintaining efficient patient management in hospitals without constant radiologic services. A series of investigations has been published with focus on diagnosis of spinal disorders in the various radiologic modalities [46,47]. A recent systematic review by Azimi et al has identified more than 40 studies that implemented NNs for diagnosis of spine disorders.…”
Section: Pathology Detection and Classificationmentioning
confidence: 99%